Peptidyl-Prolyl Cis/Trans Isomerase Pin1 and Alzheimer’s Disease - Wang, Long; Zhou, Ying; Chen, Dongmei; Lee, Tae Ho (Frontiers in Cell and Developmental Biology, 2020)
Alzheimer’s disease (AD) is the most common cause of dementia with cognitive decline. The neuropathology of AD is characterized by intracellular aggregation of neurofibrillary tangles consisting of hyperphosphorylated tau and extracellular deposition of senile plaques composed of beta-amyloid peptides derived from amyloid precursor protein (APP). The peptidyl-prolyl cis/trans isomerase Pin1 binds to phosphorylated serine or threonine residues preceding proline and regulates the biological functions of its substrates. Although Pin1 is tightly regulated under physiological conditions, Pin1 deregulation in the brain contributes to the development of neurodegenerative diseases, including AD. In this review, we discuss the expression and regulatory mechanisms of Pin1 in AD. We also focus on the molecular mechanisms by which Pin1 controls two major proteins, tau and APP, after phosphorylation and their signaling cascades. Moreover, the major impact of Pin1 deregulation on the progression of AD in animal models is discussed. This information will lead to a better understanding of Pin1 signaling pathways in the brain and may provide therapeutic options for the treatment of AD.